Effect of pecto-intercostal fascial block on extubation time in patients undergoing cardiac surgery: A randomized controlled trial - Wang, Lu; Jiang, Luyang; Xin, Ling; Jiang, Bailin; Chen, Yu; Feng, Yi (Frontiers in Surgery, 2023)
Objectives Epidural and paravertebral block reduce the extubation time in patients undergoing surgery under general anesthesia but are relatively contraindicated in heparinized patients due to the potential risk of hematoma. The Pecto-intercostal fascial block (PIFB) is an alternative in such patients. Methods This is a single-center randomized controlled trial. Patients scheduled for elective open cardiac surgery were randomized at a 1:1 ratio to receive PIFB (30 ml 0.3% ropivacaine plus 2.5 mg dexamethasone on each side) or saline (30 ml normal saline on each side) after induction of general anesthesia. The primary outcome was extubation time after surgery. Secondary outcomes included opioid consumption during surgery, postoperative pain scores, adverse events related to opioids, and length of stay in the hospital. Results A total of 50 patients (mean age: 61.8 years; 34 men) were randomized (25 in each group). The surgeries included sole coronary artery bypass grafting in 38 patients, sole valve surgery in three patients, and both procedures in the remaining nine patients. Cardiopulmonary bypass was used in 20 (40%) patients. The time to extubation was 9.4 ± 4.1 h in the PIFB group vs. 12.1 ± 4.6 h in the control group (p = 0.031). Opioid (sufentanil) consumption during surgery was 153.2 ± 48.3 and 199.4 ± 51.7 μg, respectively (p = 0.002). In comparison to the control group, the PIFB group had a lower pain score while coughing (1.45 ± 1.43 vs. 3.00 ± 1.71, p = 0.021) and a similar pain score at rest at 12 h after surgery. The two groups did not differ in the rate of adverse events. Conclusions PIFB decreased the time to extubation in patients undergoing cardiac surgery. Trial Registration This trial is registered at the Chinese Clinical Trial Registry (ChiCTR2100052743) on November 4, 2021.